Effect of Phenamiphos on Heterodera schachtii and Meloidogyne javanica - Greco, N. (Society of Nematologists, 1980)
Aqueous solutions of technical-grade phenamiphos [ethyl 3-methyl-4-(methylthio) phenyl (1-methylethyl) phosphoratnidale] were used in hatching chambers to test, under laboratory tory conditions, the effect of phenamiphos on the hatching and movement of Meloiclogyne javanica and Heterodera schachtii. Hatch of M. javanica and H. schachtii eggs was depressed 70 and 88% by nematicide at 0.48 and 4.80 μg/ml, respectively. The infectivity of second-stage larvae of both species was affected by concentrations as low as 0.01 μg/ml. At least 0.5 μg/ml was required to decrease the movement of larvae of M. javanica and H. schachtii. To decrease the movement of H. schachtii males toward females, 10 μg/ml was required. In a field experiment using a 15% granular formulation, 5 kg/ha a.i. significantly reduced infection of sugarbeet roots by H. schachtii.